Penatalaksanaan Holistik Hiperkolesterolemia pada Ibu Rumah Tangga - Semadela Solichin Putri; TA Larasati (Majority, 2020)
Hypercholesterolemia is a common metabolic condition and is characterized by a high level of plasma cholesterol, also a risk factor for developing cardiovascular diseases. Cardiovascular diseases is included in Non-Communicable Diseases (NCD). The highest proportion of deaths from NCD are cardiovascular diseases (39%), followed by cancer (27%), other NCD (30%) and diabetes mellitus (4%). The incidence of hypercholesterolemia is associated with risk factors due to unhealthy lifestyle. Proper management besides pharmacological therapy is balanced with lifestyle interventions, such as diet, exercise, smoking cessation and weight loss. Implementation of family doctor services based on evidence based medicine in patients by identifying risk factors, clinical problems, and providing holistic and comprehensive management with patient centered and family focused approach. This study is a case report with primary data sources is obtained through anamnesis (autoanamnesis and alloanamnesis), physical examination and laboratory test. Activities that this study carried out are home visits and completing family fostered sheets, from the data obtained determined a holistic diagnosis and appropriate management. A 48-year-old housewife with hypercholesterolemia, functional degree one, lack of knowledge about her illness, poor diet and exercise patterns and her treatment pattern is still curative. Identification of internal factors, i.e genetic, overweight, lifestyle and psychological. External factors, the cultural aspects of the family that do not depend with the medicine prescribed by doctors as well as environmental aspects that do not support physical activity. The patient and her family have been educated about the disease, medicine, lifestyle, and proper diet. After evaluation, found that there are changes in lifestyle and patient perceptions regarding the disease. Patient management with the principles of family medicine care is helpful to reduce health problems in patients with hypercholesterolemia.